THE ASPECTS OF ATTITUDES TOWARDS CHINESE WRITING AMONG CHINESE LANGUAGE LEARNERS - LIN LIN, TUNG (Universiti Malaysia Sarawak (UNIMAS), 2020)
Current study was aimed to investigate the Chinese language learners’ attitudes towards writing Chinese in terms of various aspects. The research objectives were to identify the affective, behavioral, cognitive, and overall attitudes towards writing in Chinese language. Survey which is one of the quantitative research designs was employed in this study among 100 undergraduates from various local universities. To conduct the survey, an attitude questionnaire was created in Google Form by adapting the questionnaire in previous studies that is Abidin, Pour-Mohammadi & Alzwari (2012) and Podsen (1997). The questionnaire was formed of two sections where the first section inquires the respondents’ demographic profile whereas the second section was separated into three units namely affective, behavioral, and cognitive components of attitude. The findings indicated that the respondents were having a positive attitude in terms of affective aspect that rated a 3.53 mean score. Besides, the students’ behavioral attitude was found neutral with a 3.29 mean score while their cognitive attitude was neutral as well with a 3.38 mean score. Lastly, the students’ overall attitudes towards writing in Chinese were found neutral with a 3.40 mean score. These findings denoted that the students’ behavioral and cognitive attitudes should be given attention and enhanced. As attitudes towards writing in a target language could influence one’s success in that language (Hashemian & Heidari, 2012), the awareness of students’ attitudes could be raised, and the strategies would be put into action to avoid the negative impacts on learners’ writing skills after this study has been conducted.